2018
DOI: 10.1111/nyas.13676
|View full text |Cite
|
Sign up to set email alerts
|

Surgical robotics for esophageal cancer

Abstract: We present an update on robotic techniques and their advantages and use in esophageal cancer surgery. Recent work has shown tremendous progress in robotic-assisted minimally invasive esophagectomy (RAMIE) and lymphadenectomy for esophageal cancer, as well as benefits of robotic surgery in high upper esophageal tumors and T4b disease. We discuss the different RAMIE techniques, especially for intrathoracic anastomosis. The ongoing ROBOT trial had demonstrated superiority of robotic esophageal cancer surgery over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Combined with the dexterity of the articulating instruments, a very precise dissection of the esophagus is facilitated, even in difficult areas along the tissue planes of the surrounding structures. [21][22][23] These features may well improve the radical resection rate for downstaged cT4b tumors, which is pivotal in achieving good oncologic outcomes.…”
mentioning
confidence: 99%
“…Combined with the dexterity of the articulating instruments, a very precise dissection of the esophagus is facilitated, even in difficult areas along the tissue planes of the surrounding structures. [21][22][23] These features may well improve the radical resection rate for downstaged cT4b tumors, which is pivotal in achieving good oncologic outcomes.…”
mentioning
confidence: 99%
“…The most common techniques have narrowed to stapled versus continuous hand-sewn anastomoses, 33 but recently also included robotic-assisted anastomoses. 34 In pediatric esophageal surgery, robot-assisted esophageal surgery has only been conducted experimentally in swine. 35,36 Concerning staplers, we have previously shown that their use is currently not advisable due to size discrepancy between staplers and patient's anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are various potential technical advantages of robots over conventional thoracoscopy, Grimminger and colleagues [1] hold the view that surgical robot and thoracoscopy were both minimally invasive approaches that applied the same steps and approaches. The benefits of the robot are therefore not fully realized.…”
Section: Discussionmentioning
confidence: 99%